2020
DOI: 10.3390/molecules25173846
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Related Members of the Aromatic Polyketide Group in Human Health and Disease: Do They Really Work?

Abstract: Some aromatic polyketides such as dietary flavonoids have gained reputation as miraculous molecules with preeminent beneficial effects on human health, for example, as antioxidants. However, there is little conclusive evidence that dietary flavonoids provide significant leads for developing more effective drugs, as the majority appears to be of negligible medicinal importance. Some aromatic polyketides of limited distribution have shown more interesting medicinal properties and additional research should be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 162 publications
0
10
0
Order By: Relevance
“…Various research groups have reported the hepatoprotective potential of naringenin [ 11 , 96 , 97 , 98 , 99 , 100 , 101 ], which is attributed to its potential in neutralizing the ROS via increased expression and activation of antioxidant enzymes [ 102 , 103 ] and the ability to amend gamma-glutamylcysteine synthetase (GGT) enzyme activity, which is involved in the GSH synthesis pathway [ 104 , 105 , 106 ]. Reportedly, pre-treatment with naringenin causes a decline in levels of AST and ALT, while antioxidant parameters, viz GPx, SOD, CAT, and GSH, have shown a significant increase [ 101 , 107 ]. The groups of rats intoxicated with CCl4 have shown repression of caspase-3 and -9 levels [ 108 ].…”
Section: Pharmacological Properties Of Naringeninmentioning
confidence: 99%
“…Various research groups have reported the hepatoprotective potential of naringenin [ 11 , 96 , 97 , 98 , 99 , 100 , 101 ], which is attributed to its potential in neutralizing the ROS via increased expression and activation of antioxidant enzymes [ 102 , 103 ] and the ability to amend gamma-glutamylcysteine synthetase (GGT) enzyme activity, which is involved in the GSH synthesis pathway [ 104 , 105 , 106 ]. Reportedly, pre-treatment with naringenin causes a decline in levels of AST and ALT, while antioxidant parameters, viz GPx, SOD, CAT, and GSH, have shown a significant increase [ 101 , 107 ]. The groups of rats intoxicated with CCl4 have shown repression of caspase-3 and -9 levels [ 108 ].…”
Section: Pharmacological Properties Of Naringeninmentioning
confidence: 99%
“…Flavonoids 30-34 (Figure 3) are characterized as a class of polyphenols with polyhydroxylated 2-phenylchromen-4-one backbone [149]. Except the simplest, penimethavone A (30), all the other members of this group 31-34 are monoglycosylated with glucose or galactose.…”
Section: Flavonoidsmentioning
confidence: 99%
“…However, despite their potential as a source of therapeutic drugs, only a few isolated flavonoids have, thus far, shown promise, since many of them have significant drawbacks due to their poor bioavailability, low water solubility, rapid metabolism and excretion, or possible adverse effects. Although silymarin, a flavonoid from Silybum marianum known for protecting the liver of people who ingested Amanita phalloides has been approved in an injectable form, other phenolics such as resveratrol and curcumin have shown clinically inconsistent results [155]. Epigallocatechin gallate (EGCG), for example, exhibits many anti-cancer capabilities, such as: acting as an antioxidant and an antiinflammatory; attenuating the NFκB pathway and, thus, its target genes that are involved in tumorigenesis; inhibiting angiogenesis and metastasis; and inducing apoptosis [156].…”
Section: Flavonoids As Therapeutic Agentsmentioning
confidence: 99%